Revisiting the hybridization processes in the triatoma brasiliensis complex (Hemiptera, triatominae): Reproductive isolation between triatoma petrocchiae and T. b. brasiliensis and T. lenti - Delgado, Luiza Maria Grzyb [UNESP]; de Oliveira, Jader [UNESP]; Ravazi, Amanda [UNESP]; Madeira, Fernanda Fernandez [UNESP]; Dos Reis, Yago Visinho [UNESP]; Pinotti, Heloisa [UNESP]; de Oliveira, Ana Beatriz Bortolozo [UNESP]; Masarin, Isabella da Silva [UNESP]; Lilioso, Maurício; Folly-Ramos, Elaine; Galvão, Cleber; de Azeredo-Oliveira, Maria Tercília Vilela [UNESP]; et al. (MDPI, 2021)
Triatoma petrocchiae is a species morphologically similar to T. b. brasiliensis (which resulted in a synonymization event); despite this similarity, genetic, morphological, and experimental crossbreed-ing studies confirmed the specific status of T. petrocchiae. Considering that both species have been reported living in sympatry and that, for a long time, most species of the T. brasiliensis complex were considered only chromatic variants of T. b. brasiliensis, we carried out experimental crosses between T. b. brasiliensis and T. petrocchiae (to confirm whether these species are reproductively isolated) and between T. lenti and T. petrocchiae (to assess whether T. petrocchiae also presents prezygotic isolation with the other species of the T. brasiliensis complex). Reciprocal experimental crosses were conducted, and weekly, the eggs were collected, counted, and separated in new containers to assess the hatch rate. Neither cross resulted in hybrids, demonstrating that there are pre-zygotic reproductive barriers installed between T. petrocchiae and the other species of the T. brasiliensis complex. On the basis of the results above, we demonstrated that T. petrocchiae is reproductively isolated from T. b. brasilien-sis and T. lenti. Furthermore, we suggest that T. petrocchiae is the species most derived from the T. brasiliensis complex.
Keywords: Chagas disease vectors; Hybridization; Reproductive barriers; Speciation; Triatomines